Search-Based Refactoring using Unfolding of Graph Transformation Systems - Qayum, Fawad; Heckel, Reiko (Electronic Communications of the EASST, 2011)
To improve scalability and understandability of search-based refactoring, in this paper, we propose a formulation based on graph transformation which allows us to make use of partial order semantics and an associated analysis technique, the approximated unfolding of graph transformation systems. We use graphs to represent object-oriented software architectures at the class level and graph transformations to describe their refactoring operations. In the unfolding we can identify dependencies and conflicts between refactoring steps leading to an implicit and therefore more scalable representation of the search space. An optimisation algorithm based on the Ant Colony paradigm is used to explore this search space, aiming to find a sequence of refactoring steps that leads to the best design at a minimal costs.